Perceptions of teacher educators about their pedagogical practices - Guimarães, Thiago Santos; Massena, Elisa Prestes; Siqueira, Maxwell Roger da Purificação (Universidade Estadual de Campinas, 2020)
Over the last few years, there have been significant changes regarding the scope of higher education institutions in the country, and this has provoked discussions about the search to meet the new training needs and the challenges presented at this level of education. Thus, it is important to underline the importance of understanding the role of university professors and the need they have to modify their teaching actions in times of constant social and technological advances. In this sense, the aim of this study was to analyze the perceptions of these teacher educators about their pedagogical practices. In this study, we will present the results of a semi-structured questionnaire with six questions, answered by fourteen teacher trainers of the undergraduate courses in Chemistry, Physics and Biology of a public university in the country. Data analysis was performed through Discursive Textual Analysis. The results indicate that teacher educators who can make a direct relationship between theory and pedagogical practices are committed to the teaching profession and seek new strategies to use in their classes, which aims to facilitate and encourage the process of teaching and learning of undergraduates. To this end, we believe that the efforts and commitments of both teacher educators and higher education institutions are necessary in order to improve university education.